3D printing of free-standing Ti3C2Tx/PEO architecture for electromagnetic interference shielding. (30th November 2021) - Hong, Sung Yong; Sun, Yan; Lee, Jinwoo; Yifei, Ma; Wang, Mei; Nam, Jae-Do; Suhr, Jonghwan
Abstract: Recently, two-dimensional (2D) MXenes have emerged as filler materials for electromagnetic interference (EMI) shielding polymer composites due to their extraordinary electrical conductivity, high surface area, hydrophilic nature, and flexibility. Three-dimensional (3D) Printing with MXenes appears to be a new paradigm for manufacturing EMI shielding structures, where complex and specific 3D architecture is often required. In this study, composite inks incorporating 2D Ti3 C2 Tx MXenes with highly thixotropic properties were developed for the liquid deposition modeling (LDM) 3D Printing method. The use of these inks enabled the fabrication of semi-transparent EMI shielding 3D architectures. The 3D-Printed EMI shields exhibited excellent EMI shielding effectiveness (EMI SE), particularly in the X-band (∼231 dB/mm) and semi-transparency (54.61%) in the visible light range. Moreover, excellent thermal management capability with highly anisotropic thermal conductivity (anisotropic index: 3.6) was achieved through 3D Printing. It is anticipated that the approach developed in this study has potential for the fabrication of advanced EMI shielding architecture with good thermal management capability for various applications, for example, precision wireless communication devices using variable frequencies with multiple channels, autonomous driving vehicles, and the Internet of Things (IoT). Graphical abstract: Image 1 Highlights: Highly thixotropic 3D printable MXene composite inks was developed. Thixotropy of the inks were implemented by numerous hydrogen bonding. Free standing MXene composite architectures for EMI shielding were 3D printed. Highly anisotropic thermal conductivity were achieved by 3D printing.